2021
DOI: 10.1093/jac/dkab093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of remdesivir in patients with COVID-19: a systematic review and network meta-analysis of randomized controlled trials

Abstract: Objectives We performed a systematic review and network meta-analysis of randomized controlled trials (RCTs) to provide updated information regarding the clinical efficacy of remdesivir in treating coronavirus disease 2019 (COVID-19). Methods PubMed, Embase, Cochrane Library, clinical trial registries of ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform were searched for relevant articles publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 34 publications
6
54
0
Order By: Relevance
“…In vitro testing has also shown that RDV has activity against SARS-CoV-2 and data from literature described the possible benefits of early initiation of RDV, especially within 10 days from clinical symptom onset, in term of shorter time to recovery, along with low risk of side effects or adverse events compared to placebo or comparators [9][10] . Despite controversial data on the efficacy of RDV in the context of COVID-19 infection, RDV remains one of the main promising compound in the setting of viral infections as Ebola, Marburg or Mers-CoV viruses [11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro testing has also shown that RDV has activity against SARS-CoV-2 and data from literature described the possible benefits of early initiation of RDV, especially within 10 days from clinical symptom onset, in term of shorter time to recovery, along with low risk of side effects or adverse events compared to placebo or comparators [9][10] . Despite controversial data on the efficacy of RDV in the context of COVID-19 infection, RDV remains one of the main promising compound in the setting of viral infections as Ebola, Marburg or Mers-CoV viruses [11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The observation that there is room for improvement in the dosing regimen is in line with clinical trials that report a shorter time to recovery [ 1 , 48 ], newer meta-analyses that support a slightly reduced mortality [ 7 ] and recent findings that the viral load declines more quickly in patients receiving remdesivir [ 11 ]. We therefore would like to argue specifically for more dose-ranging and dose-fractionation trials.…”
Section: Discussionmentioning
confidence: 71%
“…Parallelly, Goldman et al compared a 5-day regimen of remdesivir versus a 10-day course and despite noticing a trend toward better outcomes in patients receiving it for 5 days, the differences were not statistically significant [ 47 ]. These results have been compared with those of a meta-analysis published online in March 2021, where five of the RCTs included in this systematic review are analysed [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this meta-analysis reveals that those who received a 5-day remdesivir therapy had greater clinical improvement compared to those in the control group (OR = 1.68; 95% CI = 1.18–2.40). On the other hand, no statistically significant differences were observed between those with a 10-day remdesivir regimen and those receiving placebo (OR = 1.23; 95% CI = 0.90–1.68) [ 88 ].…”
Section: Discussionmentioning
confidence: 99%